1985
DOI: 10.1152/ajprenal.1985.248.1.f31
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and morphological responses of the rat kidney to reduced dietary protein

Abstract: Renal physiological and morphological adjustments to a reduced protein diet were studied in young Munich-Wistar rats. Two groups of animals were used for the correlative physiological-morphological studies: normal protein (NP, 24% dietary protein) rats and reduced protein (LP, 8% dietary protein) rats. Both groups were fed their respective diets for 4-5 wk and had free access to drinking water. Physiological measurements of GFR and urea clearance were made on five animals from each group. These data showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…In rats fed a low protein diet, fractional excretion of urea is significantly reduced compared to rats fed normal or high protein diets, consistent with stimulation ofurea reabsorption by protein restriction (1,5,8,10,12). Moreover, the normal inner medullary urea concentration profile is reversed by restricting dietary protein (1)(2)(3). In rats fed a low protein diet, the maximum inner medullary urea concentration is not found near the papillary tip, but instead, is near the base of the inner medulla (1-3), corresponding to the location of the initial inner medullary collecting duct (IMCD)l (20,21).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…In rats fed a low protein diet, fractional excretion of urea is significantly reduced compared to rats fed normal or high protein diets, consistent with stimulation ofurea reabsorption by protein restriction (1,5,8,10,12). Moreover, the normal inner medullary urea concentration profile is reversed by restricting dietary protein (1)(2)(3). In rats fed a low protein diet, the maximum inner medullary urea concentration is not found near the papillary tip, but instead, is near the base of the inner medulla (1-3), corresponding to the location of the initial inner medullary collecting duct (IMCD)l (20,21).…”
Section: Introductionmentioning
confidence: 84%
“…In rats fed a low protein diet, the maximum inner medullary urea concentration is not found near the papillary tip, but instead, is near the base of the inner medulla (1-3), corresponding to the location of the initial inner medullary collecting duct (IMCD)l (20,21). Taken together, these data suggest that a low protein diet might induce active urea transport in the IMCD (1)(2)(3)22).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…It is well known that a low protein diet reduces maximum urinary concentrating ability, reduces the fractional excretion of urea, and reverses the normal inner medullary urea concentration gradient so that the maximum inner medullary urea concentration is at the base of the inner medulla, corresponding to the location of the initial IMCD, rather than at the papillary tip (13)(14)(15)(16). Micropuncture studies had suggested the possibility of active urea reabsorption in the collecting duct from rats fed a low protein diet (17,18), but could not prove or characterize active urea transport because -T1 (PC.er AR) Control 0mM Na* Recovery of the inability to measure the urea gradient across the collecting duct in vivo.…”
Section: Discussionmentioning
confidence: 99%